Endothelial Progenitor Cells in Diabetic Vasculopathy - Anna Meiliana; Andi Wijaya (The Prodia Education and Research Institute (PERI), 2009)
BACKGROUND: The discovery of endothelial progenitor cell (EPC) a decade ago by Asahara, et al has refuted the previous belief that vasculogenesis only occurs during embryogenesis. The reduced circulating concentration of EPCs is a surrogate marker of endothelial function and has been implicated in the pathogenesis of many vascular diseases.CONTENT: Diabetes is linked to impaired vascular function, including alterations in both endothelial cells and EPCs. A number of studies have shown that individuals with diabetes have decreased level of circulating EPCs and that the severity of disease is inversely proportional to EPC levels. In vitro, hyperglycemia increases the rate of EPC senescence and the angiogenic function of EPCs from patients with either type 1 or type 2 diabetes is impaired such that they are poorly proliferative and fail to incorporate into forming vessel-like structures. Given the comprehensive role of EPC alterations in diabetes complications, modulation of the levels and/or function of EPCs may be considered a potential therapeutic strategy.SUMMARY: The available data demonstrating that decrease or dysfunction of EPCs may have a prominent role in the pathogenesis of all diabetes complications. Further approaches, such as EPC administration, may represent novel treatments for diabetic vasculopathy in the future. To date, many barriers remain to such a therapeutic approach. Firstly, there is no specific marker for EPC at present. Secondly, techniques of EPC isolation are not standardized, preventing direct comparison between various studies. The long-term effects of transplanted EPCs are currently unknown.